Successful Treatment of Acute Kidney Injury on Chronic Kidney Disease Due to Tubulointerstitial Nephritis and Acute Tubular Necrosis With Steroids and Mycophenolate Mofetil: A Case Report (Pakistan Journal of Kidney Diseases, 2026)
Acute tubulointerstitial nephritis causes interstitial inflammation and tubular injury leading to acute kidney injury which can present as rapid decline in renal function. Early diagnosis and prompt treatment is essential. After taking informed consent from our patient we present a case report where a patient with chronic kidney disease presented with rapid decline of renal function. Furthermore, renal biopsy revealed the diagnosis of tubulointerstitial nephritis. She was later started on steroids and mycophenolate mofetil, to which she responded adequately. From this case we conclude that steroids and mycophenolate mofetil are helpful in treatment in acute tubulointerstitial nephritis.